Revaluating Igbo Political Communication: A Pathway to Achieving an Igbo Presidency - Aruku, Kalita Joseph; Mensah, Eyamba; Ewhenikang, Denis Inakefe; Ikangkang, Joseph (International Journal of Humanities, Education, and Social Sciences, 2024)
There have been a long cry of marginalization from the majority people in the Southeast political zone of Nigeria who are largely Igbos. This cry has been expressed through various ways ranging from a demand for a Biafra Republic and a demand for an Igbo presidency. With various attempts made to actualize this goal failing, many youths from the zone have resorted to self help which is threatening the already precarious security situation we have in the country. This paper undertakes an in-depth analysis of the Igbo political communication strategy, identifying the strengths, weaknesses, opportunities, and threats (SWOT analysis) that have hindered progress towards an Igbo presidency. The paper identified; Ineffective communication strategies, tribal and identity based political messages, lack of political co-ordination and lack of strategic partnership among other issues as the major challenges of the Igbo political communication approach. The paper concluded that the absence of a clear, well-defined message has resulted in confusion and mistrust among potential allies and supporters and the time has come for the Igbo community to revaluate and restrategize its political communication approach by adopting a more effective communication strategy, so as to increase its chances of achieving an Igbo presidency and promoting a more inclusive, and peaceful Nigeria.